PENGARUH NILAI PERUSAHAAN DAN KINERJA KEUANGAN TERHADAP KOMPENSASI EKSEKUTIF: STUDI KASUS PADA SEKTOR KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2018-2020 - Dwi Urip Wardoyo; Isrina Octy Indah Pertiwi; Ruby Rasgiar Maulid (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
Executive compensation is a gift to an executive in return for services or rewardsfor work that has been carried out. This study aims to determine the effect of firmvalue and financial performance on executive compensation. The first hypothesisin this study is that financial performance has an effect on executive compensationand the second hypothesis is that firm value has an effect on executivecompensation. The sample of this study is the financial sector listed on theIndonesia Stock Exchange in 2018-2020 using purposive sampling. This study usesdescriptive quantitative research methods. The data in this study were tested usingthe multiple linear regression method. The results of this study are financialperformance has no effect on executive compensation and firm value has no effecton executive compensation